Research progress on catalytic preparation of fructose and lactic acid from biomass waste - WANG Yuxuan; GUO Fenfen; JIANG Zhicheng; TANG Aoyi; LIANG Yuan; KONG Lingzhao* (能源环境保护)
The massive consumption of fossil energy and growing environmental awareness have driven a global demand for green, low-carbon, and renewable energy. Utilizing organic solid waste resourcing is crucial in achieving green and circular development. Biomass waste, with its abundant supply and low cost, is a valuable renewable material for solving energy and environmental problems. Glucose, the main structure unit of biomass, holds the key to transforming biomass waste into valuable productions through its efficient conversion. To promote the high-value and high-quality conversion of biomass waste downstream, this paper reviews the processing and production characteristics of catalytic conversion of biomass waste. It focuses on summarizing the research progress and technical challenges associated with the catalytic conversion of glucose, the primary product of biomass hydrolysis, to produce fructose and lactic acid. The paper compares the effects of different catalyst materials and reaction conditions on the yield and selectivity of fructose and lactic acid production from glucose, and analyzes the advantages and disadvantages of different conversion methods. Finally, the paper proposes key areas for breakthrough to address the current issues and challenges in the research field, aiming to provide practical guidance for the resourceful treatment of organic solid waste.